A new eco-friendly dipping system for PA66 fiber cords/rubber composites with strong interfacial adhesion and good fatigue stability. (15th March 2023) - Huang, Wei; Li, Yingzhe; Zhao, Hui; Wang, Wencai; Yu, Bing; Ning, Nanying; Tian, Ming; Zhang, Liqun
Abstract: Fiber-reinforced rubber composites (FRRC) are widely used in automobile, aero tires, and conveyor belts, etc. In order to obtain high performance of FRRC, strong interfacial adhesion between fibers and rubber is a key. Resorcinol-formaldehyde-rubber latex (RFL) as the widely used dipping system in industry can do harm to human health and environment because of the release of resorcinol and formaldehyde in air. In this study, a new kind of eco-friendly dipping system for PA66 fibers was designed and successfully prepared, especially to meet the harsh service environment of aero tires. Such new dipping system is composed of the first coating of tea polyphenols (TP) on fiber surface through the hydrogen bonding between TP and PA66 fibers followed by the second coating with the mixture of glycerol triglycidyl ether (GTE), 2-ethyl-4-methylimidazole (MZ) and styrene-butadiene-vinyl-pyridine (VP) latex, in which the covalent bonding between TP and GTE, the crosslinking of GTE and the co-crosslinking of VP and NR matrix result in the formation of a solid transition bridge between PA66 fibers and NR matrix. By using such eco-friendly dipping system with optimized ratio of MZ/GTE, PA66 fibers/NR composites exhibit equivalent interfacial adhesion and aging stability as that using RFL system, while maintaining the strength and safety of composites. More importantly, PA66 fibers using the eco-friendly dipping system exhibit even better fatigue stability of interfacial adhesion after 46800 times of cyclic fatigue than that using RFL system. The relationship between the dipping layer structure and the interfacial adhesion of the composites was established. Graphical abstract: Image 1 Highlights: A new kind of eco-friendly dipping system for PA66 fiber cords was developed. The new dipping system shows equivalent adhesion effect as that using RFL. The new dipping system exhibits better fatigue stability than that using RFL. The dipping layer structure and interfacial adhesion relationship was established.